Sobre a elaboração das normas jurídicas Regarding the process of making laws - Taka Oguisso; Maria José Schmidt (SciELO, 1999)
RESUMO Este trabalho apresenta uma síntese simplificada do processo de elaboração de lei, a partir de sua conceituação jurídica, requisitos, hierarquia das normas, etapas da tramitação nas duas casas do Congresso Nacional, necessidade de quorum e sanção presidencial até um projeto de lei ser transformado em lei. Tem por objetivo auxiliar os enfermeiros e outras pessoas interessadas no assunto a participar no desenvolvimento de sua profissão através de leis que atendam melhor aos interesses profissionais da classe. ABSTRACT This paper presents a simplified summary of the process to make laws. It starts from the juridical concepts, requirements needed, hierarchy of the Brazilian laws, the need to follow proper steps through channels and committees within. The National Congress, quorum required until its final approval with the presidential sanction, when a project of law becomes an enacted law. The purpose is to help nurses anal other interested people to participate in the development of their profession. through, laws which better fulfill the professional interests of the group.